Tapajobaetis, a remarkable new genus of Baetidae with spatulate claws (Ephemeroptera) - Boldrini, Rafael (Annales de Limnologie, 2020)
The Baetidae family is represented by 32 genera from the Neotropics. A new genus, Tapajobaetis, and a new species, T. labiosus, are described based on nymphs and adults from the Brazilian Amazon region. The nymph, with highly modified head and mouth parts is readily distinguished from other genera of this family by the following combination of characters: presence of fine, simple setae on scape and pedicel, labial and maxillary palpi elongated, hind wing pads vestigial, and claws spatulate, with about 140 denticles. Adults, on the other hand, are more similar to other Baetidae and are characterized by the absence of hind wings, anteronotal protuberance slightly truncate and genitalia with posterior margin of subgenital plate convex, forceps segment III elongate. The nymphs were found exclusively over leaves of Thurnia sphaerocephala (Thurniaceae), in areas with moderate currents, and possess modification in the labial palp, which seems to be adapted to collect fine material. © EDP Sciences, 2017.